Diseño de un modelo de selección de personal por competencias para las farmacias franquiciadas a la distribuidora farmacéutica ecuatoriana Difare S.A., en la ciudad de Quito - Urbano Jiménez, Paúl Vladimir (2015)
The company DIFARE S.A., was founded in 1984, is business has stimulated day after day in the Distribution, Development of Pharmacies and Representations of Products, has allowed them to reach major coverage in points of national sale, between pharmacies, sub-distributors and wholesalers of the pharmaceutical channel and of consumption. The Human Talent has turned into the basic axis for the company because thanks to it positive results are demonstrated; and with the zeal to expire with a constant improvement one presents the following project, which has the intention of facilitating to the franchised drugstores DIFARE S.A., in the city of Quito (FARMACIA CRUZ AZUL), of the design of a model staff selection for Competitions, which will serve to minimize the job turnover. With the creation of the model of staff selection for competitions, the company will have a better planning of the process, to the moment to contract to the Human Talent adapted for the working place, since strategies and steps will be established to continuing with which it could determine constant the intellectual and human capacity of the staff, stimulating and motivating this way the personal and professional development of every person, remembering every day that departs from the overcoming of the company it is thanks to his personal overcoming. How much better be profile that be create, bigger be possibilities of success in the staff selection, the have as objective search of select to the staff correct that can identity and integrate easily in the culture of the company.